Biofilm Responses to Experimental Nutrient Enrichment of Forest Streams: Light and Nutrients Interact to Increase Biomass, and Phosphorus Alters Stoichiometry - Phillip M. Bumpers; Jonathan P. Benstead; Vladislav Gulis; John S. Kominoski; John C. Maerz; David W. P. Manning; Seth J. Wenger; Amy D. Rosemond (Ecosystems, 2025)
Nutrient enrichment of aquatic ecosystems typically results in increased algal biomass, but the response magnitude is predicted to be attenuated in light-limited ecosystems. We tested the effects of experimental nutrient enrichment in small, highly shaded forest streams and compared responses of biofilm biomass and biofilm stoichiometry, which may be less sensitive to light. After one year of pre-treatment data collection, we enriched five streams continuously for 2 years with different ratios of nitrogen (N) and phosphorus (P), which allowed us to test the relative effect of N and P on two measures of biomass—chlorophyll a (Chl a ) and ash-free dry mass (AFDM)—and on biofilm stoichiometry (C:N, C:P, and N:P) monthly. Biomass increased in response to light and both nutrients; annual average Chl a increased 9.28 × and AFDM increased 1.13 × Biofilm stoichiometry was driven largely by streamwater P concentration, with greatest effects of experimental enrichments on C:P (0.58 ×) and N:P (0.79 ×). Biofilm C:P and N:P increased across the streamwater N:P gradient. Light had only weak effects on biofilm C:P and N:P ratios, suggesting biofilm stoichiometry could function as a useful indicator of nutrient pollution when light limitation might otherwise dampen changes in biomass. The lowest C:N and C:P ratios were associated with increased Chl a :AFDM ratios, indicating increased autotrophic contributions were associated with greater N and P content. Even in low-light environments, we detected relatively large responses of algae-containing biofilms to N and P enrichment, consistent with previously reported effects of experimental nutrient addition, including primary and secondary consumer growth and production.